An Autopsy based Study on the Relationship of Cystic Artery with Respect to Common Bile Duct, Common Hepatic Duct and Calot’s Triangle in Light of Hepato-Biliary Surgery - Puloma Chakraborty; Sayak Sovan Dutta; Sandip Mukhopadhyay (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The arterial system of human body is often subjected to a good number of variations. Therefore, trying to find out variations in relationship of cystic artery with CBD, CHD and Calot’s triangle will surely be a useful endeavor for an Anatomist and Autopsy Surgeon, moreover such an effort will help the surgeons in planning and operating upon the hepatobiliary system. Method: The present work was carried out in the Department of FMT, NRSMCH, Kolkata in collaboration with the Department of Anatomy, Medical College, Kolkata over a period of one year to find out relationship of Cystic artery with CBD and CHD and also to check whether Cystic artery was present within Calot’s triangle. Fifty cadavers of both sexes were subjected to detail dissection method based on inclusion and exclusion criteria. Adult human cadavers above 18 yrs of age were included in this study whereas paediatric cadavers below 18 yrs of age, cadavers above 18 years where dissection cannot be done because of pathology in and around porta hepatis, decomposed dead bodies and dead bodies came for autopsy with gross abdominal injury involving hepato-billiary system were excluded from the study. The study was prospective, cross sectional, observational, autopsy based study. The cystic artery was lying posterior to CHD or CBD in 90% cases where as it was placed anteriorly in 10% of specimens. The cystic artery was lying anterior to CHD in 6% cases whereas and anterior to the CBD in 4% cases. In these 4 % cases CA was also inferior in position with respect to the cystic duct. In 96% of specimens the cystic artery was lying inside the Calot’s triangle whereas the 4% cases showed presence of cystic arteries outside the Calot’s triangle. Conclusion: Because variations are very common in hepatic and Cystic arteries, sound knowledge will allow the surgeons to practice safe laparoscopic or open Cholecystectomy, liver resections and vascular recombination in transplantation and there by avoid errors and patient morbidity. A good knowledge of Calot’s triangle is important for conventional and laparoscopic Cholecystectomy.